2015
DOI: 10.1364/boe.6.000815
|View full text |Cite
|
Sign up to set email alerts
|

2-D PSTD Simulation of focusing monochromatic light through a macroscopic scattering medium via optical phase conjugation

Abstract: By employing the pseudospectral time-domain (PSTD)simulation technique, we analyze the propagation of monochromatic light through a macroscopic scattering medium. Simulation results show that, monochromatic light can be directed through a scattering medium and focus into a narrow peak; a range of wavelengths has been simulated. Furthermore, we compare: i) focusing monochromatic light through a macroscopic scattering medium, and, ii) focusing monochromatic light through vacuum. Based upon numerical solutions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Various solutions proposed so far, including optical clearing method [6][7][8], may be applicable in some situations, but a universal method that can fundamentally reduce multiple scattering-related decoherence without physically altering the sample has yet to be discovered. To remedy this situation, wavefront shaping, which has been successfully utilized for various other purposes [9][10][11][12][13][14][15][16][17][18], was recently applied for the first time to OCT [19,20]. The experimental results suggested that the penetration depth can indeed be extended.…”
Section: Introductionmentioning
confidence: 99%
“…Various solutions proposed so far, including optical clearing method [6][7][8], may be applicable in some situations, but a universal method that can fundamentally reduce multiple scattering-related decoherence without physically altering the sample has yet to be discovered. To remedy this situation, wavefront shaping, which has been successfully utilized for various other purposes [9][10][11][12][13][14][15][16][17][18], was recently applied for the first time to OCT [19,20]. The experimental results suggested that the penetration depth can indeed be extended.…”
Section: Introductionmentioning
confidence: 99%